Food Products and Digital Tools: The Unexpected Interconnections - Marra, Francesco (Frontiers in Nutrition, 2022)
This work is aimed to discuss the current advances and to propose future directions in the use of science based digital tools in food product design, highlighting some unexpected interconnections among tools science based and tools thought for other purposes. The paper is structured in two main parts: an overview of the literature on the work done to explore food related apps and social media for understanding consumers' perception and preferences; a discussion on the integration of consumers’ perception and preferences in a wider scheme for food product design based on prediction of product features using advanced multiscale and hybrid methods for the design of food product features associated to consumer perception and preferences. Understanding consumer needs and preferences and linking them to product features will benefit start-uppers and researchers who develop tools for reinventing food product design.